The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11165-020-09980-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Early Childhood Science Education: Comparative Analysis of Australian and Finnish Curricula

Abstract: This research is a comparative study of Finnish and Australian science curricula in early childhood education (EC). The study aims to figure out the constructivist components of the science curriculum in two countries as well as locate the similarities and differences in the rationale and aims, contents, learning outcomes, learning activities, teacher’s role and assessment. The curriculum analysis framework developed by Van den Akker (2003) was used as a methodological framework for the curricula analysis. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
4
0
3
Order By: Relevance
“…Recent research has shown interesting similarities and differences between the Australian and the Finnish curricula. For example, similarities and differences related to equity and generic competences are debated in primary school level (see Hardy & Uljens, 2018), global citizenship and acceptance of diversity learning in foreign language learning in ECE (Garvis et al, 2018), and integration of learning and teaching delivery in the context of science learning in ECE (Havu-Nuutinen et al, 2022). Since comparative curriculum analysis regarding DC in ECE is rare, it is valuable to find out possible similarities and differences between the Australian and the Finnish ECE curricula texts.…”
Section: / 17mentioning
confidence: 99%
“…Recent research has shown interesting similarities and differences between the Australian and the Finnish curricula. For example, similarities and differences related to equity and generic competences are debated in primary school level (see Hardy & Uljens, 2018), global citizenship and acceptance of diversity learning in foreign language learning in ECE (Garvis et al, 2018), and integration of learning and teaching delivery in the context of science learning in ECE (Havu-Nuutinen et al, 2022). Since comparative curriculum analysis regarding DC in ECE is rare, it is valuable to find out possible similarities and differences between the Australian and the Finnish ECE curricula texts.…”
Section: / 17mentioning
confidence: 99%
“…A nível internacional a preconização do ensino das ciências para todos e desde os primeiros anos tem vindo a ser discutida desde o século XX com a finalidade de contribuir para o desenvolvimento da literacia científica de todos os cidadãos (Harlen & Qualter, 2018;International Science Council, 2021;OCDE, 2006). A educação em ciências desde os primeiros anos contribui para: a interpretação de fenómenos naturais decorrentes do quotidiano das crianças; a compreensão de fenómenos mais complexos em ciclos de ensino subsequentes; o despertar da curiosidade das crianças; e a promoção do gosto pelas ciências (Martins, 2020).…”
Section: Enquadramento Teóricounclassified
“…Misalnya, saat mengeksplorasi dan berinteraksi dengan lingkungannya, anak-anak mengembangkan kompetensi penamaan fenomena dan menggunakan konsep yang berbeda, yang mempromosikan pengetahuan dan multiliterasi mereka. Anak belajar menggunakan konsep sains yang berhubungan dengan alam seperti latihan mengidentifikasi spesies tumbuhan (Havu-Nuutinen et al, 2022).…”
Section: Pengenalan Manfaat Togeunclassified